2022
DOI: 10.1007/s12311-022-01471-8
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical Trial-Ready Patient Cohorts for Multiple System Atrophy: Coupling Biospecimen and iPSC Banking to Longitudinal Deep-Phenotyping

Abstract: Multiple system atrophy (MSA) is a fatal neurodegenerative disease of unknown etiology characterized by widespread aggregation of the protein alpha-synuclein in neurons and glia. Its orphan status, biological relationship to Parkinson’s disease (PD), and rapid progression have sparked interest in drug development. One significant obstacle to therapeutics is disease heterogeneity. Here, we share our process of developing a clinical trial-ready cohort of MSA patients (69 patients in 2 years) within an outpatient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 89 publications
0
8
0
Order By: Relevance
“…The Brigham and Women's Hospital (BWH) P + A + MSA clinic and MSA-MyTrial Program work in close coordination to recruit MSA patients for accurate diagnosis, longitudinal biometric and biomarker assessment, with a view to pivoting from natural history to target-engagement studies for a variety of potential investigator-or industry-sponsored therapies. Fourteen participants with a clinically probable or clinically established MSA diagnosis were evaluated for participation in this study 29 . Three subjects were deemed ineligible due to insu cient diagnostic certainty or an alternative diagnosis under consideration.…”
Section: Participants and Clinical Msa Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…The Brigham and Women's Hospital (BWH) P + A + MSA clinic and MSA-MyTrial Program work in close coordination to recruit MSA patients for accurate diagnosis, longitudinal biometric and biomarker assessment, with a view to pivoting from natural history to target-engagement studies for a variety of potential investigator-or industry-sponsored therapies. Fourteen participants with a clinically probable or clinically established MSA diagnosis were evaluated for participation in this study 29 . Three subjects were deemed ineligible due to insu cient diagnostic certainty or an alternative diagnosis under consideration.…”
Section: Participants and Clinical Msa Diagnosismentioning
confidence: 99%
“…In the current observational cohort study, we sought to exploit exciting advances in αSyn biomarkers to improve upon current clinical consensus criteria for MSA. We recruited patients who met the consensus criteria for probable or established MSA and were eligible for the ongoing clinical trials for MSA within the Brigham and Women's Hospital MSA Center of Excellence and Harvard Biomarkers Study MyTrial-MSA Program 29 . We combined brain imaging with the αSyn [18F]ACI-12589 PET tracer with a skin-based αSyn-SAA to simultaneously acquire conformational and spatial information about αSyn pathology.…”
Section: Introductionmentioning
confidence: 99%
“…An early (biomarker-assisted) diagnosis and accurate distinction from other late-onset ataxias will be crucial for MSA-C trials. 4,32 In SCAs, several recent studies have shown nonlinear progression patterns of SARA score, depending on disease stage, and inclusion of mildly affected patients was suggested to be beneficial in terms of sample size requirements. 9,11,12 Finally, large interindividual differences in disease evolution have also been described in FRDA, which were mainly related to age of onset.…”
Section: Implications and Challenges For Clinical Trial Designmentioning
confidence: 99%
“…A second key question for all types of degenerative ataxia that is closely related to the choice of outcome measures concerns the selection of participants. An early (biomarker‐assisted) diagnosis and accurate distinction from other late‐onset ataxias will be crucial for MSA‐C trials 4,32 . In SCAs, several recent studies have shown nonlinear progression patterns of SARA score, depending on disease stage, and inclusion of mildly affected patients was suggested to be beneficial in terms of sample size requirements 9,11,12 .…”
Section: Implications and Challenges For Clinical Trial Designmentioning
confidence: 99%
“…Achieving protocol standardization in neuro-urological research is challenging due to variations in clinical practices, diagnostic criteria, and treatment approaches among different centers. This problem can be solved by creating unified guidelines [ 49 ] and standardizing treatment protocols, as well as through extensive disease group stratification strategies prior to clinical trial enrollment, involving deep clinical phenotyping, imaging, and biobanking [ 50 ].…”
Section: Applications Of Biobanking In Neuro-urologymentioning
confidence: 99%